Human resource aspects of quality driven organisations in Singapore. - Lee, Sue Lynn. (2008)
The objective of this study is to establish the level of participation/involvement of Human Resource Management to Total Quality Management in Quality driven organisations in Singapore. It aims to establish whether many strategies practised by Human Resource professionals to contribute to Total Quality initiatives were applicable in Singapore.